Neuroprotective effect of nicotine against kainic acid excitotoxicity is associated with alpha-bungarotoxin insensitive receptors subtype of nAChRs - Riljak, Vladimír; Benes, Jan; Pokorný, Jaroslav; Myslivecek, Jaromir (Neuro-endocrinology letters, 2011)
OBJECTIVES: Our previous study showed that administration of nicotine is capable to protect the neurons of hippocampus against the kainic acid induced damage. Here we tested the hypotheses that multiple nicotine administration would prevent the effects of kainic acid on neuronal nicotinic receptor subtypes densities (α-bungarotoxin sensitive and α-bungarotoxin insentive) and on hippocampal cell degeneration. METHODS: Radioligand binding study was used to detect the particular nAChR subtypes densities. Two histochemical methods (bis-benzimide staining and Fluoro-Jade B dye) were used to detect and evaluate neuronal degeneration. RESULTS: Our study shows that: a) kainic acid single administration increased the number of α-bungarotoxin insentive nicotinic receptors, b) nicotine was able to prevent such changes, c) repeated nicotine administration is capable to attenuate the damage of CA1 and CA3 areas of the hippocampus. No effect on α-bungarotoxin sentive nicotinic receptors was observed. Our data therefore reveal the importance of α-bungarotoxin insentive nicotinic receptors in the response to kainite and the ability of nicotine to prevent such changes both in the cell degeneration and in number of receptors. CONCLUSION: Nicotine administration influences α-bungarotoxin insensitive receptors and repeated administration is capable to protect against toxicity caused by kainic acid in hippocampal area.
Keywords: Animals; hipokampus; Rats, Wistar; Receptors, Nicotinic; Bungarotoxins; nikotin; kyselina kainová; neurony; Neurons; agonisté excitačních aminokyselin; Neuroprotective Agents; nikotinové receptory; Protein Isoforms; Excitatory Amino Acid Agonists; radioligandová zkouška; bungarotoxiny; krysa rodu Rattus; Hippocampus; Kainic Acid; Radioligand Assay; protein - isoformy; zvířata; nikotinoví agonisté; Nicotine; Nicotinic Agonists; Rats; potkani Wistar; neuroprotektivní látky